Xeric grasslands of the inner-alpine dry valleys of Austria – new insights into syntaxonomy, diversity and ecology - Martin Magnes; Wolfgang Willner; Monika Janišová; Helmut Mayrhofer; Elías Afif Khouri; Christian Berg; Anna Kuzemko; Philipp Kirschner; Riccardo Guarino; Harald Rötzer; Elena Belonovskaya; Asun Berastegi; et al. (Vegetation Classification and Survey (VCS), 2021)
Aims: We studied the syntaxonomic position, biodiversity, ecological features, nature conservation value and current status of dry grasslands investigated by Josias Braun-Blanquet more than 60 years ago. Study area: Inner-alpine valleys of Austria. Methods: We sampled 67 plots of 10 m2, following the standardized EDGG methodology. We subjected our plots to an unsupervised classification with the modified TWINSPAN algorithm and interpreted the branches of the dendrogram syntaxonomically. Biodiversity, structural and ecological characteristics of the resulting vegetation units at association and order level were compared by ANOVAs. Results: All the examined grasslands belong to the class Festuco-Brometea. From ten distinguished clusters, we could assign four clusters to validly published associations, while the remaining six clusters were named tentatively. We classified them into three orders: Stipo-Festucetalia pallentis (Armerio elongatae-Potentilletum arenariae, Phleo phleoidis-Pulsatilletum nigricantis, Medicago minima-Melica ciliata community, Koelerio pyramidatae-Teucrietum montani), Festucetalia valesiacae (Sempervivum tectorum-Festuca valesiaca community); Brachypodietalia pinnati (Astragalo onobrychidis-Brometum erecti, Agrostis capillaris-Avenula adsurgens community, Anthericum ramosum-Brachypodium pinnatum community, Ranunculus bulbosus-Festuca rubra community, Carduus defloratus-Brachypodium pinnatum community). Conclusions: The ten distinguished dry grassland communities of the Austrian inner-alpine valleys differ in their ecological affinities as well as their vascular plant, bryophyte and lichen diversity. We point out their high nature conservation importance, as each of them presents a unique habitat of high value. Taxonomic reference: Names of vascular plants, bryophytes and lichens follow Fischer et al. (2008), Frahm and Frey (2004) and Nimis et al. (2018), respectively. Syntaxonomic reference: Names of orders and classes follow Mucina et al. (2016), references for associations and alliances are given in the text. Abbreviations: ANOVA = analysis of variance; DCA: detrended correspondence analyses; EDGG: Eurasian Dry Grassland Group; EIV: ecological indicator value; FL: Fließ; GR: Griffen; GU: Gulsen; KA: Kaunerberg; LA: Laudegg castle in Ladis; MA: Marin; NM: Neumarkt in der Steiermark; OM: Obermauern; PÖ: Pöls; PU: Puxer Loch; TWINSPAN = Two-way indicator species analysis; ZS: Zinizachspitze.